Faktor-Faktor Yang Mempengaruhi Firm Value Pada Perusahaan Manufaktur (Jurnal Paradigma Akuntansi, 2022)
This research aimed to obtain empirical evidence about the effect of profitability, firm size, intellectual capital and good corporate governance on firm value. This study used 84 data samples of manufacturing company listed on the Indonesia Stock Exchange from 2017-2019. This study used Eviews 11 program to process data. Sample was selected using purposive sampling method. The statistical method used to test the hypothesis was the multiple linear regression. The results of this research showed that profitability, firm size and intellectual capital had no effect on firm value, while good corporate governance had a positive effect on firm value. The implication of this research is the need to improve management performance in managing its assets to generate profits, determine strategies, and supervise company operations to increase company value which will provide good signals for investors.